Table of Content - - (Journal of medical and pharmaceutical sciences, 2023)
Table of Content: 1. The effect of using some medicinal plants in the treatment of pain and inflammation in Abdali farms in the State of Kuwait Mrs. Enas Abdulaziz Alsarawi 2. Lifestyle and nutrition of the Gulf countries students living in the UK Dr. Manal Amro Almughamisi, Dr. Ameerah Mohammed Khairi Almaski 3. Childhood and Adolescent Overweight, Obesity and Socio-Economic Circumstances in The Gulf Cooperation Council Countries: A Systematic Review Dr. Manal Amro Almughamisi, Dr. Majella O’Keeffe, Prof. Seeromanie Harding 4. Assessment of Hospitalised Patient Satisfaction with Nursing Care in the Gynaecology and Obstetrics Department of Benghazi Medical Center, Libya Lecturer / Fatma Abdalla Atitalla Omar , Lecturer / Fathi Saad Mustafa , Dr. Randa Mahmoud Gadalla Elamrony 5. Assessing knowledge of Pediatric Diabetes Mellitus among Nurses at Turaif General Hospital, Saudi Arabia Ziyad Osailan Alruwaili , Waajid Awad Alanzi, Ayesh Hussein Alhazmi, Mansur Mohammd Alrwaili 6. Job Satisfaction and Associated Factors among Healthcare Workers at King Fahad University Hospital in Al-Khobar Maram Habib Hussain Alali